ELECTION 2024: OPEN PROPORTIONAL OR CLOSED PROPORTIONAL SYSTEM - Agus Mulyono (SEAN Institute, 2023)
This study aims to compare two electoral systems, namely open and closed proportional systems in the context of the 2024 Indonesian general election (Pemilu). This research was conducted by analyzing the advantages and disadvantages of each system, as well as their impact on the quality of political representation and voter participation. The research method used is literature analysis and secondary data from previous general elections, as well as interviews with political experts and policy makers. The results showed that open and closed proportional systems have their respective advantages and disadvantages. However, in the context of Indonesia which has complex political and social diversity, for the 2024 general election a closed proportional system is more suitable to be implemented because it can minimize vote counting time so as to minimize casualties due to fatigue, lower costs of holding elections and avoid high political costs so that can prevent potential corruption. Therefore, the recommendation from this study is to implement a closed proportional system in the 2024 election .